2007
DOI: 10.1002/pmic.200600703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aluminum‐responsive proteins in rice roots by a proteomic approach: Cysteine synthase as a key player in Al response

Abstract: Aluminum (Al) toxicity is a serious limitation to worldwide crop production. Rice is one of the most Al-tolerant crops and also serves as an important monocot model plant. This study aims to identify Al-responsive proteins in rice, based on evidence that Al resistance is an inducible process. Two Al treatment systems were applied in the study: Al 31 -containing simple Ca solution culture and Al 31-containing complete nutrient solution culture. Proteins prepared from rice roots were separated by 2-DE. The 2-DE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 61 publications
7
138
1
4
Order By: Relevance
“…In roots of rice seedlings, expression of genes related to sulfur metabolism, including ATP sulfurylases, are up-regulated in response to Al (Yang et al, 2007). This response is possibly connected to down-regulation of miRNA395, since our analysis showed that miRNA395 expression was reduced after 8 h of Al treatment (Figures 2 and 3).…”
Section: Metabolism Of Nutrients and Carbonmentioning
confidence: 69%
See 1 more Smart Citation
“…In roots of rice seedlings, expression of genes related to sulfur metabolism, including ATP sulfurylases, are up-regulated in response to Al (Yang et al, 2007). This response is possibly connected to down-regulation of miRNA395, since our analysis showed that miRNA395 expression was reduced after 8 h of Al treatment (Figures 2 and 3).…”
Section: Metabolism Of Nutrients and Carbonmentioning
confidence: 69%
“…Differential display reverse transcription PCR has been used to identify genes that respond to Al in rice cultivars displaying different sensitivities to this metal. Among the genes identified, several were related to signal transduction, ion transport, cellular metabolism, stress, and cytoskeleton rearrangements (Yang et al, 2007). Two genes, OsSTAR1 encoding a nucleotide binding domain, and OsSTAR2, found to be a bacterial-type ABC gene, being expressed mainly in roots, conferred Al tolerance in rice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a high concentra- tion of heavy metal treatment induces the production of heavy metal-resistance proteins. They could resist the toxicity of heavy metal [27]. During the later period of treatment, the decline of soluble protein contents could be explained that the Cd-induced oxidative stress appeared [26] and the protein synthesizing machinery was impaired due to the Cd effect [28].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes help to protect cells from oxidative stress. GST has been observed to be upregulated in Arabidopsis and rice that have been exposed to Al (Ezaki et al 2004, Yang et al 2007. The GR and GST results clearly indicate that Al is inducing the enhanced activities of the enzymes, which is occurring more dramatically in Icatu.…”
Section: Discussionmentioning
confidence: 69%